Analisis Penangkapan Terduga Teroris oleh Detasemen Khusus 88 Anti-Teror dari Perspektif Penegakan Hukum-Joseph Goldstein - Marthsian Yeksi Anakotta; Erwin Bernard Ubrwarin; Roni Gunawan Raja Gukguk (Fakultas Hukum, Universitas Internasional Batam, 2021)
Densus 88 AT is a special police unit that has the duty and authority to enforce the law on criminal acts of terrorism. As law enforcers, Densus 88 AT has the authority to carry out the arrest of suspected terrorists based on Law No. 5/2018. Based on the theory of law enforcement by Joseph Goldstein, law enforcement is divided into three areas, namely: total enforcement, full enforcement, and actual enforcement. This paper is a law-normative research which aims to identify and understand the arrest of suspected terrorists by Densus 88 AT from the perspective of law enforcement by Joseph Goldstein. The conclusions are as follows: the status of a suspect is unknown in the Indonesian Criminal Code; Densus 88 AT has the authority to arrest suspected terrorists based on RI Law Number 5 of 2018; and in the three areas of law enforcement, Densus 88 AT has discretionary power in three areas of discretion, namely: choosing objectives, intervention methods, and field procedures.